Qur’an Teachers’ Creativity in Classroom Management to Improve Sixth Grade Students’ Qur’anic Reading and Memorization Skills at SDIT Al Uswah Tuban - Ulum, Syaroful (Journal of Educational Research and Practice, 2024)
Creativity is defined as the discovery or creation of a new idea or an idea that has never existed before. Creativity is also understood as any productive effort that is unique to an individual. A person is considered creative if they solve problems or engage in activities using approaches that are different from those used by others. Usually, creativity is surprising, causes people to comment with admiration, and tends to be enjoyable. Some people say that creativity is a talent one is born with. This statement is not entirely true. Creativity is the result of learning, habituation, and experiences processed by the brain. Creativity is the product of the cooperation between the right and left hemispheres of the brain, combining the work of imagination and real conditions. Creativity is 1% idea and 99% action. No matter how small the teacher's effort in managing the class, whether it is singing, storytelling, playing movement or clapping games (ice breaking), riddles, or any concentration games, these activities will greatly impact the students who directly experience the rhythm and atmosphere of the class. Daily reading, writing, and memorizing can become very boring routines for children. Sometimes, a class may consist of various children's characters coming together. This certainly requires the teacher's creativity in conducting the learning process. Even just opening and closing lessons with motivation, cheers, songs, and other activities significantly influence students' abilities in reading and memorizing the Qur'an.